A rua como espaço para morar: observações sobre a apropriação dos espaços públicos pelos moradores de rua da cidade de João Pessoa-PB - Oliveira, Maria do Rosário de Lima (2011)
This study deals with the results of observations of the homeless city of João Pessoa, in order to identify the presence of this population in the city's public spaces. In the formation of urban centers, public spaces are places of passage of society which is constantly moving. But there is a segment of the population seeking to adapt to a way of living in that space, after suffering disruptions in all its bonds: so is the trajectory of the homeless in cities. This reality is also found in the city of João Pessoa, place preparation of this research. Identify the homeless as one that appropriates public space to live is what guides the methodology used - the ethnographic research. For this application, however, was made a route to gain access to the subject, which is not easily distinguished among those who appropriate public space just as they develop activities for sustenance. The routine monitoring of a charity that works with the homeless in the city of João Pessoa was the guiding point of access, which culminated in observations and listening to stories, which are also presented in this paper. Thus, it was possible to identify the homeless and know your way of living, which is not just to adapt to public space - even in rejection of the rest of society - but in a way, even if silent, screaming for her right to dignity inherent in every human being.